Estimation of costs and returns from dairying in Malwa region of Madhya Pradesh - CHAND, PREM; SIROHI, SMITA; MISHRA, ANUPAM; CHAHAL, V P (The Indian Journal of Animal Sciences, 2017)
The study was carried out on 300 milk producing households in Malwa region of Madhya Pradesh to estimate the costs and returns from milk production at farm household level. The individual animal-wise and household-wise costs were estimated using software Milk Production Economics Analysis Package (MILKEcAP:1.0 & 2.0). The findings of the analysis revealed that the overall gross maintenance cost/animal/year in the zone was least (rupees 126.33/animal/day) in case of local cow and highest for crossbred cattle (rupees 169.51/animal/day). The variable costs accounted for nearly 3/4th of the total costs irrespective of category of animals. Feed cost accounted highest to the total costs and it was relatively higher in case of buffalo. The overall cost per litre of milk was highest (rupees 24.84) for buffalo, and lowest for crossbred cow (rupees 22.26). However, due to variability in milk yield, there were wide variability in net economic margins. The net economic margins were almost negligible (rupees 0.62/l) in local cow, comparatively higher in crossbred cow (rupees 2.55/l) and fairly good in buffalo (rupees 5.03/l).